(untitled) (Actual Problems of Psychology in Educational Institutions, 2022)
This article highlights the definition of interpersonal relationships, their functions and influence on the activity of a personality. The role of communication and its importance are formulated, the problem of interpersonal relationships among youth is disclosed, the issue of relationships within student groups in particular. With regard to the current everyday-life difficulties, the main goal of this article is to research СOVID-19 pandemic’s influence on the level of interpersonal relationships among students before quarantine restrictions and after. Therefore, the empirical research among the students was held by the means of questionnaire. This article presents and analyses the results of the experiment connected to the understanding of the СOVID-19 pandemic’s influence on the level of interpersonal relationships of youth.